1992
DOI: 10.1152/jn.1992.67.4.961
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal responses to static texture patterns in area V1 of the alert macaque monkey

Abstract: 1. We recorded responses from neurons in area V1 of the alert macaque monkey to textured patterns modeled after stimuli used in psychophysical experiments of pop-out. Neuronal responses to a single oriented line segment placed within a cell's classical receptive field (CRF) were compared with responses in which the center element was surrounded by rings of elements placed entirely outside the CRF. The orientations of the surround elements either matched the center element, were orthogonal to it, or were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

83
744
5
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 946 publications
(843 citation statements)
references
References 0 publications
83
744
5
4
Order By: Relevance
“…The same authors called these latter neurons ''uniform cells.'' Similar data were obtained for alert monkeys (Knierim and van Essen 1992): 32% orientation contrast cells and 6% uniform cells. …”
Section: Models Of Non-crf Inhibitionsupporting
confidence: 82%
See 3 more Smart Citations
“…The same authors called these latter neurons ''uniform cells.'' Similar data were obtained for alert monkeys (Knierim and van Essen 1992): 32% orientation contrast cells and 6% uniform cells. …”
Section: Models Of Non-crf Inhibitionsupporting
confidence: 82%
“…For instance, response suppression by a bar texture surround outside the CRF was found in nearly 80% of all orientation-selective cells reported in Knierim and van Essen (1992) and Nothdurft et al (1999). Although only approximately one third of the cells showed dependence of the effect on the orientation of the texture surrounding the CRF, these authors suggested that this type of differential suppression might be the possible source of the pop-out effect in orientation contrast experiments (Fig.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Certain contextual configurations result in pop-out which enhance stimulus detection (Nothdurft 1993;Wang et al 1994;Braun and Julesz 1998), while others result in crowding and impair stimulus detection (Pelli et al 2004). Neural correlates of these perceptual phenomena have been found in sensory visual areas, where responses to a stimulus in the classical receptive field (CRF) are facilitated or suppressed by stimuli presented in the non-classical receptive field (nCRF) (Knierim and van Essen 1992;Polat et al 1998;Jones et al 2002;Schwabe et al 2006;Ichida et al 2007). Whether context facilitates or suppresses responses depends on a variety of factors, including luminance contrast of the target.…”
Section: Introductionmentioning
confidence: 99%